Reliability Analysis and Robust Design of Metal Forming Process - Li, Bing (My University, 2008)
Metal forming processes have been widely applied in many industries. With the severe competition in the market, a reliable and robust metal forming process becomes crucial for the manufacturer to reduce product development time and cost. For the purpose of supplying engineers with an effective tool for a reliable and robust design of metal forming process, this research investigates the application of traditional reliability theory and robust design methods in metal forming processes for the ultimate goal of increasing quality and reducing cost in manufacturing.
A method to assess the probability of failure of the process based on traditional reliability theory and the forming limit diagram (FLD) is presented. The forming limit of a material is chosen as the failure criteria for analysis of reliability.
A study of prediction of forming limit diagrams using finite element simulation without pre-defined geometrical imperfection or material imperfection is presented. A 3D model of the dome test is used to predict the FLD for AA 5182-0. The FE predicted forming limit diagram is in good agreement with the experimental one. The uncertainty sources for the scatter of forming limits are categorized and investigated to see their effects on the shape of FLD.
A novel method of improving the reliability of a forming process using the Taguchi method at the design stage is presented. The thickness-thinning ratio is chosen as the failure criteria for the reliability analysis of the process. A Taguchi orthogonal array is constructed to evaluate the effects of design parameters on the thinning ratio. A series of finite element simulations is conducted according to the established orthogonal array. Based on the simulation results, Taguchi S/N analysis and ANOVA analysis are applied to identify the optimal combination of design parameters for minimum thinning ratio, minimum variance of thinning ratio, and maximum expected process reliability.
A multi-objective optimization approach is presented, which simultaneously maximizes the bulge ratio and minimizes the thinning ratio for a tube hydroforming process. Taguchi method and finite element simulations are used to eliminate the parameters insignificant to the process quality performance. The significant parameters are then optimized to achieve the multiple optimization objectives. The optimization problem is solved by using a goal attainment method. An illustrative case study shows the practicability of this approach and ease of use by product designers and process engineers.
Keywords: metal forming process, robust, product, reliable, design, (FLD)